ANALISIS PERENCANAAN STUDI KELAYAKAN POTENSI PANAS BUMI UNTUK PENGEMBANGAN SPA (SOLUS PER AQUA), DI KABUPATEN NGADA, PROVINSI NUSA TENGGARA TIMUR - Aperta Ledy Alam; Fiati Nurmaya (JURNAL GEOMINERBA (JURNAL GEOLOGI, MINERAL DAN BATUBARA), 2020)
Geothermal direct use activity can be also be conducted through the stages of the initial survey (preliminary), pre-feasibility study, feasibility study, utilization, and operations. Manifestation location, which is hot spring, also be disseminated at many points in Ngada Regency, East Nusa Tenggara Province. In many locations of hot spring existence, has been used for public bath. Because some location is close to public residential and is in the route of public transportation road, like as Mengeruda. The location of Mengeruda hot springs has accessibility which is asphalt road for public transportation that have 3.5 meter width. This hot springs is not too far from commercial airport, Bajawa. Several inns like small hotel and quest house, have been around location of Mengeruda hot springs. This is becoming contribution from tourism sector. Feasibility study activity consists market analysis, technical analysis, and financial analysis. These three of analysis activity will give the recommendation as output and result from feasibility study.